Growth and Production of Shallots (Allium Ascalonicum L.) at Various Dosages Cow Manure - Feriatin Feriatin; Wa Ode Amnah; Muhammad Sifa (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine the effect of cow manure dosage on the growth and production of shallots (Allium ascalonicum L.). This research was conducted in Pohorua Village, Maligano District, Muna Regency, from March to June 2020. This study used a one-factor Randomized Block Design (RAK) consisting of four treatment levels and repeated three times so that 12 experimental units were obtained. The factor studied was cow manure. The dose factors of cow manure tested were S0: without cow manure (control), S1: cow manure dose of 10 tons/ha, S2: cow manure dose of 20 tons/ha, S3: cow manure dose 30 tons/ha. The results showed that cow manure treatment had a significant effect on plant height growth, the number of leaves, the wet weight of tubers with stover, the dry weight of bulbs with stover, and the production of shallots. The best treatment for the dose of cow manure on the growth and production of shallots was S3 (quantity of 30 tons/ha), with an average output of 20.33 tons/ha.